ECO-FRIENDLY PRINTING ON COTTON WITH NATURAL MORDANTS - K. SANGAMITHIRAI*, (The Journal of Research ANGRAU, 2019)
A study was carried out to print cotton fabric with the marigold flowers as dye source, gum arabic as thickenerand eco- friendly mordants such as myrobalon and pomegranate rinds. Paste prepared using marigold flowers,myrobalon and pomegranate rinds with gum arabic as natural thickener was applied for printing on cotton fabric.Colour fastness tests were conducted to assess fastness to sunlight, washing, wet crocking and dry crocking, wetpressing and dry pressing. The printed samples exhibited moderate to good fastness to colour change. Thestaining test showed very good fastness of all samples. The unique shades and soothing effect created by naturaldyes are rewarding than the aesthetic features of chemical dyes. Marigold flowers as a natural dye along with naturalmordant and thickener can be successfully used for printing cotton fabric on a larger scale. The effect of natural dyeand mordants on print and colour fastness properties were evaluated and found to be good for printing on cotton.